1995
DOI: 10.1007/bf01268124
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy techniques in late-stage Coats'-like exudative retinal detachment

Abstract: Retinal telangiectasia is the hallmark of Coats' disease. In the late stages, leakage from these abnormal vessels can result in a total, bullous exudative retinal detachment with cholesterol-laden subretinal fluid. Secondary angle-closure glaucoma may result in a blind and painful eye which may require enucleation or evisceration. Surgical reattachment of the retina and destruction of the retinal telangiectasia may preserve these eyes. We have found that vitrectomy, internal drainage of subretinal fluid and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…3 15 16 Several authors have reported more invasive techniques, including vitrectomy, posterior retinotomy, use of intraocular silicone or gas, and scleral buckling. [17][18][19] Visual and anatomical outcomes are disappointing with these more complex and invasive techniques. We feel that this is a situation where less is more.…”
Section: Discussionmentioning
confidence: 99%
“…3 15 16 Several authors have reported more invasive techniques, including vitrectomy, posterior retinotomy, use of intraocular silicone or gas, and scleral buckling. [17][18][19] Visual and anatomical outcomes are disappointing with these more complex and invasive techniques. We feel that this is a situation where less is more.…”
Section: Discussionmentioning
confidence: 99%
“…Endolaser, however, produced good results. Yoshizumi et al observed similar findings in one advanced exudative case managed with external drainage and attempted cryotherapy then subsequent laser photocoagulation [3]. They suggest that retained cholesterol deposits insulated the retinal telangectasia preventing freezing.…”
mentioning
confidence: 66%
“…In advanced cases (stages 3 and 4), the focus of management shifts from preserving vision to preserving a painless eye. In these cases, the conventional wisdom has been to perform vitrectomy, scleral buckling cryotherapy, and drainage of the exudate via either a retinotomy or external drain [3]. …”
mentioning
confidence: 99%
“…Yoshizumi et al 5 reported success in three out of four patients with advanced Coats' disease or Coats'-like reaction after vitrectomy surgery. All three successful operations included internal air-fluid exchange and one unsuccessful operation did not include internal air-fluid exchange.…”
Section: Commentmentioning
confidence: 99%